Water Conservation Inevitable Strategy - Eyvaz, Murat; Albahnasawi, Ahmed; Gürbulak, Ercan; Yüksel, Ebubekir (IntechOpen, 2022)
To conserve water, one of the most valuable and vital resources in the world, management and public strategies, processes to reduce water consumption in industrial/commercial applications, and methods such as smart irrigation systems have been proposed. Local authorities have focused on infrastructure operations to prevent water losses and flow measurements have begun to be followed more closely. The use of greywater for partial recycling of water for household purposes and rainwater harvesting systems are being encouraged. In addition, there is more research on water conservation, its smart use, and recycling of used water being conducted. This book presents valuable scientific research on water and land management, groundwater management, and water/wastewater treatment applications for the conservation of water.